2022
DOI: 10.3389/fneur.2022.816031
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Research Trends and Identifying Hotspots of Traditional Chinese Medicine (TCM) Nursing Technology for Insomnia: A 18-Years Bibliometric Analysis of Web of Science Core Collection

Abstract: ObjectiveTo explore the research hotspot and frontier direction of TCM nursing of insomnia and provide reference for the follow-up study of the optimal scheme of TCM nursing of insomnia.BackgroundInsomnia is a common sleep-wake disorder, affects 6–10% of adults and was associated with independent higher risks of cardiovascular disease and diabetes. TCM Nursing Techniques of insomnia has a long history and has shown a definite impact. However, it's still lack of analysis in the field of the most commonly used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…A study showed that the literature production trend using bibliometric analysis in medical research was active, and more than one-third of bibliometric articles indexed in Scopus were from the medical field (21). At present, scholars have used bibliometric analysis to study treatments for insomnia and different populations' sleep disorders (22)(23)(24). But few research focused on healthy people, even on college students.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that the literature production trend using bibliometric analysis in medical research was active, and more than one-third of bibliometric articles indexed in Scopus were from the medical field (21). At present, scholars have used bibliometric analysis to study treatments for insomnia and different populations' sleep disorders (22)(23)(24). But few research focused on healthy people, even on college students.…”
Section: Introductionmentioning
confidence: 99%
“…Citation analysis is one of the main methods of bibliometrics, which can evaluate the quality and recognition of papers, and better understand the discipline construction and development of a field. At present, many TCM-related areas have been well studied and explored through bibliometric analysis, such as the analysis of research trends on Artemisinin ( Dong et al., 2022 ), TCM nursing technology for insomnia ( Wang et al., 2022 ), acupuncture research about migraine ( He et al., 2022 ), and traditional Chinese health exercises for improving cognitive function ( Li et al., 2021 ). However, there is currently no English literature published on the quantitative analysis of interactions between GM and TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong policy support for promoting TCM nursing practices in China, healthcare professionals have the opportunity to actively contribute to the advancement of TCM nursing by leveraging TCM resources. [11]…”
Section: Discussionmentioning
confidence: 99%